Residual β-Cell Function in Type 1 Diabetes Followed for 2 Years after 3C Study. (29th June 2021) - Lin, Kun; Yang, Xiaoping; Wu, Yixi; Chen, Shuru; Zeng, Qiong
Abstract : Objective . To investigate the natural history and related factors of the pancreatic β -cell function in Chinese type 1 diabetic patients from 3C study Shantou center. Method . Stimulated C-peptide levels from follow-up data of 201 individuals in 3C study Shantou subgroup starting in 2012 were used. Residual β -cell function was defined as stimulated C − peptide   level ≥ 0.2   pmol / mL, on the basis of cut-points derived from the Diabetes Control and Complications Trial (DCCT). Results . 36.8% of patients had residual β -cell function, and the percentage was 68.2% in newly diagnosed diabetic patients. COX regression analysis indicated that the age of diagnosis, HbA1C level, and duration were independent factors of residual β -cell function in individuals with ≤5 years duration, but in those with duration ≥5 years, only the age of diagnosis was a predictor. The pancreatic β -cell function mainly declined in the first 5 years of the duration, and the rate of decline was correlated negatively with the duration and age of diagnosis. Receiver operating characteristic (ROC) analysis indicated that the cut-off point of stimulated C-peptide was 0.615 pmol/mL in patients with <5 years duration to have 7% HbA1c. Conclusion . Age at diagnosis was the strongest predictor for residual C-peptide. There was a more rapid decline of stimulated C-peptide in duration ≤5 years and younger patients. Therefore, intervention therapies of β -cells should start from the early stage, and the recommended target goal of stimulated C-peptide is 0.615 pmol/mL or above.